2014
DOI: 10.1590/1981-8637201400040000091313
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anterior crossbite and its influence on gingival recession

Abstract: Several etiological factors for gingival recession have been discussed in the literature, and the vestibular region of the mandibular incisors is RESUMODiversos medicamentos vêm sendo testados e utilizados na terapia pulpar conservadora de dentes decíduos, no entanto, o formocresol continua sendo o material de escolha nas pulpotomias, mesmo não atendendo às exigências de biocompatibilidade e promovendo a fixação do tecido pulpar vital e não o seu reparo. Com o surgimento do Agregado Trióxido Mineral como um ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
0
6
0
5
Order By: Relevance
“…It was reported that orthodontic correction of dental crossbite may lead to the spontaneous improvement of periodontal tissue, as repositioning of a tooth into its proper alveolar foundation allows better distribution of forces on the long axis, as well as bone remodeling (28). At the end of treatment, we noticed an improvement in periodontal health and in the esthetics of the lower left central incisor as the tooth was reattached at its base bone.…”
Section: Discussionmentioning
confidence: 68%
“…It was reported that orthodontic correction of dental crossbite may lead to the spontaneous improvement of periodontal tissue, as repositioning of a tooth into its proper alveolar foundation allows better distribution of forces on the long axis, as well as bone remodeling (28). At the end of treatment, we noticed an improvement in periodontal health and in the esthetics of the lower left central incisor as the tooth was reattached at its base bone.…”
Section: Discussionmentioning
confidence: 68%
“…Por otra parte, Andrade et al 12 reporta un caso de mordida cruzada anterior donde se colocó un plano de levantamiento de mordida posterior con un resorte para vestibularizar el diente que se encontraba cruzado, lo cual solamente es viable cuando existe dentro del perímetro del arco el espacio para proinclinar y el diente y a su vez, cuando son mordidas cruzadas que involucran pocos dientes contrario al caso reportado en este artículo, donde se encontraban involucrados los cuatro incisivos superiores.…”
Section: Discussionunclassified
“…El tipo de terapéutica a utilizar depende de cada caso, diseñando un plan de tratamiento que se adapte a las necesidades del paciente en beneficio de corregir la maloclusión y contribuir con su adecuado crecimiento y desarrollo. Se coincide con Prakash y Durgesh, 15 Andrade et al 12 y con Ruiz y Sáez 17 ya que es necesario el levamentamiento de la mordida para la corrección de la mordida cruzada. Sin embargo, el uso de tornillos expansores depende del perímetro del arco y del análisis de espacio realizado sobre los modelos de estudio.…”
Section: Discussionunclassified
“…Nestas assertivas a maioria dos estudantes respondeu positivamente em ambas. O controle de biofilme desempenha um papel essencial na prevenção da inflamação gengival, o que poderia desencadear ou acelerar a progressão da recessão 16 . Adicionalmente, Chrysanthakopoulos 17 observou em seus achados uma associação entre tabagismo crônico e recessão gengival e mostrou um fator causal do tabagismo na doença periodontal.…”
Section: Discussionunclassified
“…Apenas as respostas corretas foram discriminadas nas tabelas, sendo que as demais respostas foram agrupadas na categoria "outras". Definido o critério de correção para as questões, o número de acertos foi somado para cada estudante, sendo que esses valores poderiam oscilar ou variar entre um e 16…”
Section: Materials E Métodounclassified